Analysis of the process of coloring objects based on the optical properties of objects - Prayogi, Soni; Silviana, Fitria; Hamid, Tarmizi (Cakrawala, 2022)
Color is a certain spectrum contained in a perfect light (white). The purpose of this study is 1). Can determine the cause of the color of the object (what causes a different object than the other color) 2). Can observe the color that occurs when two or more colors are mixed. The benefit in order to inform readers about what actually causes the color of the object and what if two or more colors are mixed. Mixing colors for color RGB, the colors Red to Green produce colors orange, blue color to produce a color Sian Green, Red color with blue produce magenta, and Red, Green with Blue produces white color. For CMY color mixing, the colors Cyan with yellow produce green color, magenta with yellow produces red color, the color Cyan by Magenta produces blue, and the colors Cyan, Magenta produces yellow Gray (Brown). Color objects can be invisible to the eye because of the reflection of the color of the object illuminated by light.